Troponin Profile Of Clopidogrel And Ticagrelor With Old Generation PPIs In Myocardial Infarction Patients - Erlisa Ika Yuni Pramesti; Kharisma Jayak Pratama; Hidayah Apriliawan (International Journal of Health Engineering and Technology, 2026)
Myocardial infarction is a leading cause of cardiovascular death in Indonesia with an increasing prevalence. The interaction of clopidogrel-ticagrelor with older-generation PPIs can affect antiplatelet efficacy and troponin levels. This study aims to describe troponin levels in the use of clopidogrel and ticagrelor with older-generation PPIs and their relationship to patient characteristics and lipid profiles. A retrospective descriptive observational method was conducted on 76 myocardial infarction patients at March eleventh University Hospital (November 2024-November 2025) using medical record data. Univariate (frequency, mean) and bivariate (Chi-Square, p<0.05) analyses were processed using SPSS. The results showed that the majority of patients were male (66%), aged 46-65 years (64%). There was no significant association between gender (p=0.542), age (p=0.415), clopidogrel-PPI (p=0.346), ticagrelor-PPI (p=0.368), and LDL (p=0.100) with troponin, but triglycerides were significantly associated (p=0.040). The average troponin of clopidogrel was 9.465 ng/L, higher than that of ticagrelor (3.879 ng/L). It was concluded that triglycerides significantly influenced troponin, while patient characteristics and the combination of antiplatelet-PPI did not.